VIEW OF ISLAMIC LAW AND CIVIL LAW ON THE DIVISION OF JOINT PROPERTY POST-DIVORCE - Alawi, Mubayyin Al; Arif, Suyud; Hakim, Hilman (JURNAL ILMU SYARIAH, 2023)
Joint property is property acquired either individually or jointly by the husband and wife during the marriage bond, regardless of the name of the item. The purpose of this research is to find out the distribution of joint assets after divorce according to Islamic law and civil law and the benefits of the research that the results of this research can provide knowledge for academics in studying law, especially marriage law. For the community as information material or input for the process of fostering legal awareness for the community to minimize the occurrence of disputes regarding the distribution of joint assets. The research method used in this writing is library research using descriptive qualitative methods or library research. The results of this study indicate that in civil law and Islamic law it is emphasized that a divorced husband and wife are each entitled to half of the joint property. only in the Civil Code there is a clause namely "without questioning which party the property comes from" this shows that the wife and husband have the same contribution to the existence of property in their marriage. We recommend that the division of joint assets be done fairly, so as not to cause injustice between what is the right of the husband and what is the right of the wife. If there is a dispute between husband and wife regarding joint property, then the settlement of the dispute is submitted to the court. Settlement through court is an option. Provisions regarding the distribution of joint assets are based on conditions accompanying a marriage relationship, such as death, divorce, and so on.